PERSPEKTIF PEMUDA TERHADAP USAHA BUDIDAYA IKAN KERAPU (Epinephelus Sp) DI KOTA AMBON - Sri Panca Rahayu; Jacobus Wilson Mosse; Yolanda M. T. N Apituley (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2023)
Ambon City is part of the Maluku Province which has very potential fisheries resources and also human resources (youth) who are expected to participate in the development of the aquaculture sector. The role of youth as the next generation is expected to be able to form perspectives in developing aquaculture businesses in the future, for this reason this research was conducted to analyze youth perspectives on grouper (Ephinephelus Sp) aquaculture in Ambon City. The sampling method for viewing youth perspectives in this study is the purposive sampling method (Sugiyono, 2015), which measures youth perspectives using a Likert Scale (Sugiyono, 2010). With a Likert Scale, the variables to be measured are translated into variable indicators (perspective of basic knowledge, cultivation techniques, interest in cultivation and cultivation business development). Based result using the likert scale that the youth’s knowledge in groupe cultivation is a very high with youth interval who involved is 2,91 more higher than youth who not involved 2,43. Tecnical knowledge about cultivation is olso higt. Youth involved knowledge about cultivation youth involved in cultivation 2,66, inversely propotional with youth who not involved in cultivation be on 1,59. Youth interest with groupe cultivation get an higher presentage 2,71 and who not interested 2,35 and related with grouper cultivation development in the future have rank 2,67 compared to the uninvolved 1,68. Generally the total number from whole perspective comparison between youth with the grouper cultivation development in Ambon is already high with interval precentege 2,40.